Impacto de las regletas Cuissenarie en el desarrollo de nociones básicas en niños de preescolar - Yánez Ronquillo, Lili del Rocio (2025)
Cuisenaire rods are educational tools commonly used in early childhood education to support the learning of fundamental mathematical concepts. Despite their widespread use, there is a lack of sufficient research validating their effectiveness, which creates challenges in fully understanding their educational impact. This research aimed to explore how Cuisenaire rods influence the development of essential skills in young children, particularly focusing on quantity recognition, comparison abilities, spatial relationships, and sensory perception. To address this, the researchers conducted a documentary review of existing studies that examine the role of Cuisenaire rods in preschool math learning. The analysis revealed that these colorful, tactile rods are particularly effective in helping children visualize abstract mathematical concepts, making them more accessible and understandable. Through hands-on, sensory-based manipulation, children are encouraged to engage actively with mathematical ideas, fostering not only comprehension of basic operations but also promoting exploration, autonomy, and the development of mathematical language. The study concluded that Cuisenaire rods serve as effective teaching tools in early education by combining visual and tactile elements, which enhance early learning outcomes. They help children build confidence in their mathematical abilities and adapt to various learning styles, making math both engaging and approachable. Beyond supporting cognitive development, the use of these rods also nurtures sensory and spatial awareness, offering a holistic learning experience. Overall, the research emphasizes the value of incorporating Cuisenaire rods into early math instruction to strengthen foundational skills and promote a positive attitude toward mathematics from a young age.